القياس المحاسبي وأثره على جودة المعلومة المالية في ظل التضخم –دراسة ميدانية- - تجاني, بشرة (Universty of Eloued جامعة الشهيد حمة لخضرالوادي, 2021)
الملخص: هدفت هذه الدراسة إلى التعرف على بدائل القياس المحاسبي في ظل ارتفاع الأسعار، ودراسة مقارنة بين التكلفة التاريخية والقيمة العادلة حول تأثيرهما في الاستخدام على جودة المعلومة المالية، كما سعت الدراسة إلى معرفة مدى تطبيق القيمة العادلة في البيئة المحاسبية الجزائرية للعمل على تحسين جودة المعلومة المالية في ظل التضخم. ولتحقيق أهداف الدراسة واختبار الفرضيات اعتمدنا على المنهج الوصفي التحليلي في الجانب النظري، وتم تطبيق منهج دراسة الحالة في الاستبيان والمنهج المقارن في تحديد الاختلاف بين التكلفة التاريخية والقيمة العادلة من أجل توفير خصائص نوعية للمعلومة المالية هذا فيما يخص الجانب التطبيقي، حيث اعتمدت الدراسة على توزيع الاستبيان على عينة تتكون من 150 فردا من أكاديميين ومهنيين وتم الابقاء على 122 مستجوب، واستخدمنا جملة من الأساليب الاحصائية والرياضية في تحليل البيانات بالإضافة إلى برنامج SPSS-V.21 ومعالج البيانات Excel. وقد توصلت الدراسة إلى أن رغم العيوب التي تشوب التكلفة التاريخية في فترات التضخم إلا أنه لا يمكن الاستغناء عنها ذلك لما توفره من ثقة في المعلومة المالية، مع العمل المزدوج للتكلفة التاريخية والقيمة العادلة في فترات التضخم لتوفير معلومات جيدة ذات نوعية من أجل تلبية احتياجات المستخدمين وهذا ما أوصت به الهيئات الدولية، كما توصلت الدراسة أيضا إلى أن البيئة المحاسبية الجزائرية يعيب عليها بعض العوائق في تطبيق القيمة العادلة والتي إن ذللت هذه العوائق يتلاءم تطبيقها في البيئة المحاسبية الجزائرية. Résumé : فرنسية أو انجلزية This study aimed to find out the alternatives of the accounting measurement under high prices, and to a comparison study between historical cost and fair value about their use impact on the quality of the financial information. The study also sought to know the extent of applying the fair value in the Algerian accounting environment to improve the quality of financial information under inflation. In order to achieve the objectives of the study and test the hypotheses, we relied on the descriptive and analytical approach in the theoretical side. For the applicative side, the case study methodology was applied in the questionnaire, and the comparative approach in determining the difference between the historical cost and the fair value in order to provide qualitative characteristics of the financial information. Whereas the study relied on the distribution of the questionnaire on a sample consisting of 150 academics and professionals, 122 respondents were retained. We used a set of statistical and mathematical methods in data analysis in addition to the SPSS-V.21 program and the Excel. The study found that despite the defects in the historical cost in periods of inflation, it cannot be dispensed with because it provides confidence in the financial information. Also, the double action of historical cost and fair value in periods of inflation to provide good quality information in order to meet the needs of users and this what was recommended by international authorities. In addition, the study also found that the Algerian accounting environment is defective by some obstacles concerning the application of fair value, which if they are eliminated, its application in the Algerian accounting environment will be appropriate.
أطروحة دكتوراه تخصص: محاسبة وتدقيق في العلوم الاقتصادية و التسيير
Keywords: قياس محاسبي- بدائل قياس محاسبي - تكلفة تاريخية- قيمة عادلة- جودة معلومة مالية- تضخم; accounting measurement - accounting measurement alternatives - historical cost - fair value - quality of financial information - inflation.